2023
DOI: 10.1111/plb.13595
|View full text |Cite
|
Sign up to set email alerts
|

Trait variation along an urban–rural gradient in Asian dayflower: the contribution of phenotypic plasticity and genetic divergence

N. Taichi,
A. Ushimaru

Abstract: Environmental changes associated with urbanisation can exert pressure that facilitates both adaptations and plastic responses in plants. Field surveys or common garden experiments (CGE) alone cannot differentiate between the observed phenotypic traits resulting from plastic responses versus evolutionary adaptations to urban environments. We conducted a field survey of habitat environmental factors and four vegetative traits in 12 Commelina communis populations along an urban–rural gradient in the Osaka‐Kobe m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…There is limited information on phenotypic trait differentiation along urban–rural gradients available for C. communis (Taichi & Ushimaru, 2024 ; Ushimaru et al., 2014 ). To understand the relationship between genetic and phenotypic trait adaptation in this species, we propose conducting trait measurements in common garden and reciprocal transplant experiments (e.g., Gorton et al., 2018 ) to determine whether diverse urban habitat populations are forced to adapt to local environments or can survive in a range of urban habitats.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited information on phenotypic trait differentiation along urban–rural gradients available for C. communis (Taichi & Ushimaru, 2024 ; Ushimaru et al., 2014 ). To understand the relationship between genetic and phenotypic trait adaptation in this species, we propose conducting trait measurements in common garden and reciprocal transplant experiments (e.g., Gorton et al., 2018 ) to determine whether diverse urban habitat populations are forced to adapt to local environments or can survive in a range of urban habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution results suggested that polyploids distribute larger and have a higher tolerance to urban environmental stresses. In urban Cc habitats, compared to rural habitats, there are higher levels of soil pH, drought, shaded, and pollinator-limited conditions (Ushimaru et al ., 2014; Taichi and Ushimaru, 2024; Taichi et al ., unpublished data). However, it is still unclear why polyploidy enables Cc to be more adaptive to such conditions compared to Ccfc with lower ploidy.…”
Section: Discussionmentioning
confidence: 99%